Evaluation of functional outcome using dual plating in treatment of intra-articular distal humerus fractures in adults - Mohammed Jaffer Jawad Al-Musawei; Mohamed Abdul Aziz; Ahmed Sarhan Mzyon (Journal of the Pakistan Medical Association, 2024)
Of all the humerus fractures in adults, 30% are of the distal end of the bone. The dual plate is strong biomechanically. The current study was conducted at Al-Yarmouk Teaching Hospital, Baghdad, Iraq, between July 1, 2019 to July 1, 2021 to study the role of dual plating in intra-articular distal humerus fractures. Included were 20 adult patients, all with intra articular fracture of the distal humerus and treated and evaluated by open reduction and internal fixation technique using dual locking plating. Clinically the final results were assessed using the Mayo Elbow Performance Score (MEPS). The final results were observed to be excellent in 12 (60 %), good in 6 (30%), fair in 2 (10 %) patients, with no poor results recorded. One patient had transient ulnar neuropraxia which recovered spontaneously after six weeks and one patient developed superficial skin infection which responded to antibiotic treatment. The mean of MEPS was significantly higher after six months and one year than that after two weeks, two months, and four months of operation. Keywords: Elbow, Distal, Articular, Fractures, Humeral, Humerusb